The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ecolmodel.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

A catch forecast model for the Peruvian scallop (Argopecten purpuratus) based on estimators of spawning stock and settlement rate

Abstract: a b s t r a c tThe Peruvian Bay scallop (Argopecten purpuratus) fishery in Independencia bay (Southern Peru) is being subjected to great inter-annual variability in catch and effort. This is mainly due to the ENSO (El Niño-Southern oscillation)-caused changes in the population dynamics of the stock, which greatly proliferated during the El Niño events 1983 and 1998. As a consequence "gold rush" conditions arose and resource users profited from a multi-million dollar export business. After the El Niño booms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Based on the model, recruitment and production increases of scallops account for this result, as scallops consume 58% of phytoplankton production during EN. Wolff et al (2007) found that the increase in scallops was likely a non-trophic effect resulting from increased larval survival in warmer temperatures. This recruitment success combined with increased oxygen concentrations is likely the main cause of the increase in fisheries yield.…”
Section: Summary Statistics Flow Structure and Maturitymentioning
confidence: 99%
“…Based on the model, recruitment and production increases of scallops account for this result, as scallops consume 58% of phytoplankton production during EN. Wolff et al (2007) found that the increase in scallops was likely a non-trophic effect resulting from increased larval survival in warmer temperatures. This recruitment success combined with increased oxygen concentrations is likely the main cause of the increase in fisheries yield.…”
Section: Summary Statistics Flow Structure and Maturitymentioning
confidence: 99%
“…When SS and SF were applied together, as done by Wolff et al (2007) for Independence Bay, the regression was not significant (R 2 = 0.362; P = 0.509). The addition of the independent variable RD increased the fit dramatically (R 2 = 0.959; P = 0.060); however, a significant regression was achieved only from the combination of the independent variables SS and RD (without SF) (R 2 = 0.916; P = 0.024*).…”
Section: Multiple Regressionmentioning
confidence: 99%
“…These events improve benthic oxygen concentrations through a lowering of the thermocline and also increased metabolic activity (respiration, somatic growth) in response to the increased temperature. New findings suggest that reduced mortality in the larval stage, due to faster development to settlement times, may be mainly responsible for population booms during EN periods (Wolff et al 2007). Our exploration of the environmental influences on the scallop stock in Sechura Bay suggests a greater importance of riverine inputs to the bay.…”
Section: Importance Of Environmental Variability and Implications Formentioning
confidence: 99%
See 2 more Smart Citations